Halogen-free flame-retardant ABS (acrylonitrile butadiene styrene) material as well as preparation method and application thereof
By adopting a halogen-free flame retardant system in ABS materials, combining ABS resin with PBT resin, aluminum phosphonate flame retardant, nitrogen-based flame retardant and compatible agent, the problem of corrosion of existing flame retardant ABS materials during processing is solved, and the V-0 flame retardant grade and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202411908386.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Among the existing enhanced flame retardant ABS materials, the bromine flame retardant system is prone to degradation during processing to produce hydrogen halide gas, corrode the mold, and the mechanical properties of the phosphorus flame retardant system are insufficiently improved.
A halogen-free flame retardant system is adopted, and V-0 flame retardant grade and excellent mechanical properties are achieved through a specific weight ratio ABS resin and PBT resin, combined with aluminum phosphonate flame retardant, nitrogen-based flame retardant and compatibilizer.
The V-0 flame retardant grade of ABS material is achieved, and the mechanical properties of halogen-free flame retardant ABS material are significantly improved, avoiding the corrosion problem of halides.
Smart Images

Figure SMS_1 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method and application of a halogen-free flame-retardant ABS material. Background Art
[0002] ABS resin contains butadiene rubber components and has a low oxygen index. It is a flammable material. In order to expand product applications, it is necessary to improve fire resistance and perform flame retardant modification. At present, mature enhanced flame retardant ABS on the market all belong to the bromine flame retardant system, which is a halogen flame retardant system. It is easy to degrade and produce small molecular hydrogen halide gas during the material processing, which corrodes the mold. Therefore, from the development trend of flame retardant material technology, the future will focus on halogen-free flame retardancy. Research and development of new halogen-free flame retardant ABS has become a hot direction for product research.
[0003] "Study on GWIT Flame Retardant Properties of ABS Polyester Alloy", authors Du Ronghua, Tang Lei and others disclosed an ABS / PBT alloy, which recorded ABS / PBT (0.75:0.25), using a bromine antimony flame retardant system, with good flame retardancy and GWIT performance. However, experiments have found that the SMA compatibilizer used in this scheme does not improve the mechanical properties of the phosphorus flame retardant system enough. Summary of the invention
[0004] The object of the present invention is to provide an ABS material with V-0 flame retardancy and good mechanical properties, and a preparation method and application thereof.
[0005] The present invention is achieved through the following technical solutions: A halogen-free flame-retardant ABS material, comprising the following components in parts by weight: ABS resin 35-46 parts; PBT resin 14-21 parts; Glass fiber 20-30 parts; 2-5 parts of toughening agent; 3-7 parts of compatibilizer; 15-20 parts of aluminum phosphonate flame retardant; 2-6 parts of nitrogen flame retardant.
[0006] The weight content of rubber in the ABS resin that can achieve the purpose of the present invention is in the range of 9-35wt%. Preferably, the weight content of rubber in the ABS resin is in the range of 18-26wt%.
[0007] Rubber content test method: Weigh a certain mass (m1) of ABS pellets, put them into a centrifuge tube (m2), dissolve them in acetone ultrasonically for ≥4 hours, and then centrifuge them in a high-speed centrifuge for more than 40 minutes at a speed of 15000~17500r / min. Remove the supernatant, wash the rubber at the bottom of the centrifuge tube with acetone solvent 3 times, dry the insoluble matter and the centrifuge tube in an oven at 80℃ for 4h, and then place them in a vacuum drying oven at 65℃ for 12 hours, weigh m3, and the rubber mass fraction is equal to m3-m2 / m1.
[0008] The weight ratio of ABS resin to PBT resin is (2-3):1; preferably, the weight ratio of ABS resin to PBT resin is (2.2-2.8):1.
[0009] Preferably, in the halogen-free flame-retardant ABS material of the present invention, the sum of the contents of PBT and ABS accounts for no less than 40 wt % of the total weight of the halogen-free flame-retardant ABS material.
[0010] The technical solution of the present invention has no special limitation on PBT. Preferably, the flow rate is measured to be 20-34 g / 10 min according to the ISO1133-1:2022 method, and the test conditions are 1.2 kg / temperature of 235°C.
[0011] The compatibilizer is selected from at least one of PMMA, PC, PETG, and ethylene-acrylate copolymer; preferably, the compatibilizer is ethylene-acrylate copolymer. These substances all contain ester structures, which have good compatibility with ABS and can play a compatibilizing and bridging role between the PBT phase and the ABS phase, thereby improving the compatibility of the two phases and achieving excellent mechanical properties.
[0012] Specifically, the melt flow rate range of PMMA is: 15-25 g / 10 min, 230 ° C, 3.8 kg; The melt flow rate range of PC is: 10-25g / 10min, 300℃, 1.2kg; The melt flow rate range of PETG is: 15-30g / 10min, 220℃, 10kg; The melt flow rate range of ethylene-acrylate copolymer is: 1-10 g / 10 min, 190°C, 2.16 kg; PMMA is polymethyl methacrylate; PC is polycarbonate; PETG is polyethylene terephthalate-1,4-cyclohexanedimethanol ester.
[0013] PMMA can be purchased from: PMMA LG2, Sumitomo Chemical Co., Ltd., Japan; PMMA CM-211, Chi Mei Co., Ltd., Taiwan, China; The ethylene-acrylate copolymer can be an ethylene-butyl acrylate copolymer, which can be purchased from: A560, DuPont, USA; 17BA 04, Arkema, France; PC can be purchased from: PC H-2000F, Mitsubishi Corporation, Japan; POLYCARBONATE RESIN TARFLONFN2200, Idemitsu, Japan; PETG can be purchased from: PETG GN071, Eastman Company, USA; CR-5511, China Resources Chemical; The toughening agent is selected from at least one of high-rubber powder, SBS and SEBS. The toughening agents are all commonly used elastomers in ABS and PBT, and have good toughening effects.
[0014] The nitrogen-based flame retardant is selected from one of melamine, melamine cyanurate and melamine polyphosphate; preferably, the nitrogen-based flame retardant is selected from melamine polyphosphate, which has good compatibility and flame retardant efficiency.
[0015] The structure of the aluminum phosphonate flame retardant is as follows:
[0016] Wherein, R1, R2, R3, R4, R5, and R6 are independently selected from -OH, -C2H5, -C6H 13 、-C8H 17 Any of the following: In the aluminum phosphonate flame retardant, R1, R2, R3, R4, R5, and R6 are all -OH; or R1, R2, R3, R4, R5, and R6 are all -C2H5; or R1, R2, R3, R4, R5, and R6 are all -C6H 13 ; or R1, R2, R3, R4, R5, and R6 are all -C8H 17 .
[0017] Preferably, in the aluminum phosphonate flame retardant, R1, R2, R3, R4, R5, and R6 are all -C2H5.
[0018] Specifically, the aluminum phosphonate flame retardant can be selected from diethyl aluminum hypophosphite, aluminum dihydrogen phosphate, and the like.
[0019] The mass ratio of the aluminum phosphonate flame retardant to the nitrogen flame retardant is 2.5-10, preferably 3.5-8, which has a higher flame retardant efficiency and achieves a flame retardant effect of V-0.
[0020] The aluminum diethylphosphinate flame retardant can be purchased from: EXOLIT OP 1230 from Clariant.
[0021] Those skilled in the art can add antioxidants and lubricants to the halogen-free flame-retardant ABS material of the present invention according to actual needs.
[0022] The antioxidant may be: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 3,5-di-tert-butyl-4-hydroxybenzyl dimethylamine; diethyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; stearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearyl-thiotriazolylamine; 2,6-di-tert-butyl-4-hydroxymethylphenol; 2,4-di-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylglycerol allyl ether)-1,3 ,5-triazine; N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid); N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; bistriethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]; 2,2'-thiodiethyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc.
[0023] The lubricant may be: at least one of stearate lubricants, fatty acid lubricants, and stearate ester lubricants; the stearate lubricant is selected from at least one of calcium stearate, magnesium stearate, and zinc stearate; the fatty acid lubricant is selected from at least one of fatty acids, fatty acid derivatives, and fatty acid esters; the stearate ester lubricant is selected from at least one of pentaerythritol stearate.
[0024] The preparation method of halogen-free flame-retardant ABS material comprises the following steps: mixing each component uniformly according to a proportion, extruding and granulating through a twin-screw extruder at a rotation speed of 300-500 rpm and a barrel temperature of 200-220° C., so as to obtain the halogen-free flame-retardant ABS material.
[0025] The application of halogen-free flame-retardant ABS materials is used in the fields of household appliance parts and office supplies.
[0026] The present invention has the following beneficial effects: The present invention uses a specific weight ratio of ABS resin and PBT resin, and can utilize the property that PBT resin is more easily charred than ABS resin to improve the flame retardancy of the resin matrix, the condensed phase flame retardant effect of the aluminum phosphonate flame retardant, and the gas phase flame retardant effect of melamine, and the three work together to achieve the V-0 flame retardant grade of the ABS material. At the same time, the compatibilizer can improve the compatibility of ABS with PBT and the aluminum phosphate flame retardant, and significantly improve the mechanical properties of the halogen-free flame-retardant ABS material of the present invention. DETAILED DESCRIPTION
[0027] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0028] The sources of raw materials used in the present invention are as follows: PBT: PBT 1084HQ, Nantong Xingchen Company, melt flow rate 22g / 10min, test conditions are 1.2kg / temperature 235℃.
[0029] ABS-A: rubber weight content 9.8%, Gaoqiao Petrochemical, ABS 275; ABS-B: rubber weight content 11.7%, Gaoqiao Petrochemical, ABS 8434; ABS-C: rubber weight content 18.5%, Guoqiao Petrochemical, ABS D-670; ABS-D: rubber weight content 25%, Guoqiao Petrochemical, ABS D-100; ABS-E: 35% rubber weight content, Chimei, Taiwan, China, PA-757; Rubber content test method: Weigh a certain mass (m1) of ABS pellets, put them into a centrifuge tube (m2), dissolve them with acetone ultrasonically for ≥4 hours, and then centrifuge them for more than 40 minutes at a speed of 15000~17500r / min in a high-speed centrifuge. Remove the supernatant, wash the rubber at the bottom of the centrifuge tube with acetone solvent 3 times, dry the insoluble matter and the centrifuge tube in an oven at 80℃ for 4 hours, and then place them in a vacuum drying oven at 65℃ for 12 hours, weigh m3, and the rubber mass fraction is equal to m3-m2 / m1; Glass fiber: ECS13-4.5-534A, China Jushi Co., Ltd. Toughening agent: high rubber powder, ABS HR POWER 181, Kumho Corporation, South Korea; Compatibilizer A: PMMA, PMMA LG2, Sumitomo Chemical Co., Ltd., Japan; Compatibilizer B: ethylene-butyl acrylate copolymer, A560, DuPont, USA; Compatibilizer C: PC, PC H-2000F, Mitsubishi Corporation, Japan; Compatibilizer D: PETG, PETG GN071, Eastman Company, USA; SMA: SMA 700, Jiaxing Huawen Chemical Co., Ltd.; Aluminum phosphonate flame retardant A: aluminum diethylphosphinate flame retardant, Clariant; Aluminum phosphonate flame retardant B: Aluminum dihydrogen phosphate, Hubei Zhonglong Kangsheng Company; Melamine polyphosphate: FR-NP, Shouguang Weidong Company; Melamine cyanurate: MCA-01, Shouguang Weidong Company; Melamine: Melamine, Shandong Aojin Chemical Company; Antioxidant: RIANOX 1010, Tianjin Lianlong New Materials Co., Ltd.; Embodiment and comparative example Preparation method of halogen-free flame-retardant ABS material: According to the ratio, the components are mixed evenly, and extruded into granules by a twin-screw extruder at a rotation speed of 300-500 rpm and a barrel temperature of 200-220° C. to obtain a halogen-free flame-retardant ABS material.
[0030] Various test methods: (1) Vertical burning: UL94 standard, test conditions: specimen thickness 1.5 mm; (2) Izod notched impact strength: ISO 180 / 1A standard, temperature 23°C, specimen thickness 4 mm; (3) Heat deformation temperature: ISO 75-1:2020 standard, test conditions: 1.8 MPa load, flat.
[0031] Table 1: Weight parts of each component and test results of halogen-free flame-retardant ABS materials of Examples 1-6 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 ABS-D 40 41.2 44.2 45 40 36.7 PBT 20 18.8 15.8 15 20 18.3 Fiberglass 25 25 25 25 30 20 Toughening agent 3 3 3 3 5 5 Compatibilizer A 5 5 5 5 7 3 Aluminum Phosphate Flame Retardant A 18 18 18 18 15 20 Melamine polyphosphate 4 4 4 4 2 6 Antioxidants 0.5 0.5 Vertical combustion V-0 V-0 V-0 V-0 V-0 V-0 <![CDATA[Notched impact strength, kJ / m 2 > 5.5 5.6 5.8 5.9 5.4 5.2 Heat deformation temperature, °C 102 105 103 100 108 100 It can be seen from Examples 1-4 that the heat deformation temperature is better when the ABS / PBT ratio is preferred, and the notched impact strength is moderate.
[0032] Table 2: Weight parts of each component and test results of halogen-free flame-retardant ABS materials of Examples 7-10 Example 7 Example 8 Example 9 Example 10 ABS-A 40 ABS-B 40 ABS-C 40 ABS-E 40 PBT 20 20 20 20 Fiberglass 25 25 25 25 Toughening agent 3 3 3 3 Compatibilizer A 5 5 5 5 Aluminum Phosphate Flame Retardant A 18 18 18 18 Melamine polyphosphate 4 4 4 4 Vertical combustion V-0 V-0 V-0 V-0 <![CDATA[Notched impact strength, kJ / m 2 > 3.7 4.4 5.2 5.9 Heat deformation temperature, °C 105 103 103 100 It can be seen from Examples 1 / 7-10 that the higher the weight content of rubber in the ABS resin, the better the notched impact strength and the slower the heat deformation temperature decreases. Preferably, when the weight content of rubber in the ABS resin is 18-26wt%, the comprehensive performance of notched impact strength and heat deformation temperature is better.
[0033] Table 3: Weight parts of each component and test results of halogen-free flame-retardant ABS materials of Examples 11-14 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 ABS-D 40 40 40 40 PBT 20 20 20 20 Fiberglass 25 25 25 25 Toughening agent 3 3 3 3 Compatibilizer A 5 Compatibilizer B 5 Compatibilizer C 5 Compatibilizer D 5 Aluminum Phosphate Flame Retardant A 18 18 18 Aluminum Phosphate Flame Retardant B 18 Melamine polyphosphate 4 4 4 4 Vertical combustion V-0 V-0 V-0 V-0 <![CDATA[Notched impact strength, kJ / m 2 > 7.8 5.8 6.3 4.5 Heat deformation temperature, °C 103 101 102 100 It can be seen from Examples 1 / 11-13 that the compatibilizer is preferably ethylene-butyl acrylate copolymer.
[0034] It can be seen from Example 1 / 14 that the flame retardant is preferably diethyl aluminum hypophosphite.
[0035] Table 4: Weight parts of each component and test results of comparative halogen-free flame-retardant ABS material Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 ABS-D 30 48 40 40 40 PBT 30 12 20 20 20 Fiberglass 25 25 25 25 25 Toughening agent 3 3 3 3 3 Compatibilizer A 5 5 5 5 SMA 5 Aluminum Phosphate Flame Retardant A 18 18 14 21 18 Melamine polyphosphate 4 4 8 1 4 Vertical combustion V-0 V-2 V-2 V-1 V-0 <![CDATA[Notched impact strength, kJ / m 2 > 4.1 6.1 5.7 5.6 2.6 Heat deformation temperature, °C 95 97 103 102 98 It can be seen from Comparative Example 1 / 2 that if the ABS content is too low, the notched impact strength and the heat deformation temperature cannot meet the requirements; if the ABS content is too high, the flame retardancy cannot reach V-0, and the heat deformation temperature cannot meet the requirements.
[0036] It can be seen from Comparative Examples 3 / 4 that when the ratio of the flame retardant is not within the scope of the present invention, the flame retardancy cannot reach V-0.
[0037] It can be seen from Comparative Example 5 that when SMA is used as a compatibilizer, the notched impact strength is insufficient.
Claims
1. A halogen-free flame-retardant ABS material, characterized in that: By weight, it includes the following components: ABS resin 35-46 parts; PBT resin 14-21 parts; Glass fiber 20-30 parts; 2-5 parts of toughening agent; 3-7 parts of compatibilizer; 15-20 parts of aluminum phosphonate flame retardant; 2-6 parts of nitrogen flame retardant.
2. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The weight content of rubber in the ABS resin is in the range of 9-35wt%, preferably 18-26wt%.
3. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The weight ratio of ABS resin to PBT resin is (2-3):1; preferably, the weight ratio of ABS resin to PBT resin is (2.2-2.8):
1.
4. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The compatibilizer is selected from at least one of PMMA, PC, PETG and ethylene-acrylate copolymer; preferably, the compatibilizer is ethylene-acrylate copolymer.
5. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The toughening agent is selected from at least one of high rubber powder, SBS and SEBS.
6. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The nitrogen-based flame retardant is selected from one of melamine, melamine cyanurate and melamine polyphosphate; preferably, the nitrogen-based flame retardant is selected from melamine polyphosphate.
7. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The structure of the aluminum phosphonate flame retardant is as follows: Wherein, R1, R2, R3, R4, R5, and R6 are independently selected from -OH, -C2H5, -C6H 13 、-C8H 17 Any of the following; Preferably, in the aluminum phosphonate flame retardant, R1, R2, R3, R4, R5, and R6 are all -OH; or R1, R2, R3, R4, R5, and R6 are all -C2H5; or R1, R2, R3, R4, R5, and R6 are all -C6H 13 ; or R1, R2, R3, R4, R5, and R6 are all -C8H 17 ; More preferably, in the aluminum phosphonate flame retardant, R1, R2, R3, R4, R5, and R6 are all -C2H5.
8. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: By weight, it also includes antioxidants and lubricants.
9. The method for preparing the halogen-free flame-retardant ABS material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder at a rotation speed of 300-500 rpm and a screw barrel temperature of 200-220° C., so as to obtain a halogen-free flame-retardant ABS material.
10. The use of the halogen-free flame-retardant ABS material according to any one of claims 1 to 8, characterized in that: Used in household appliance parts and office supplies.
Citation Information
Patent Citations
Acrylonitrile butadiene styrene (ABS) inflaming retarding material and preparation method thereof
CN102093663A
Weather-proof flame retardant ABS / PET material for extrusion process and preparation method of ABS / PET material
CN103772881A
High performance flame retardant material
CN104371253A
A halogen-free flame-retardant wear-resistant ABS composition and a preparing method thereof
CN104788878A
ABS (Acrylonitrile Butadiene Styrene) material and preparation method and application thereof
CN118027598A
Cited By
Halogen-free flame-retardant ABS material, preparation method therefor and use thereof
WO2026138259A1